Intervensi pada Populasi Risiko Tinggi Skizofrenia, Perlukah? - Ayu Nuzulia Putri; Sasanti Yuniar (Jurnal Psikiatri Surabaya, 2020)
Schizophrenia is a mental disorder with severe and persistent manifestation of psychosis symptoms chronically which patient of Schizophrenia are administered to health facilities very late. Almost people do not recognize the first symptoms even though client has genetic of Schizophrenia. There are strategies and interventions have been used to increase the number of disability. The researchers give omega-3, supportive psychotherapy and family therapy they also consider atypical antipsychotic as preventive but it still controversy.